The Effect of Financial Technology, Financial Literacy, and Financial Inclusion on Business Sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Badung Regency - Tangi, Venansia Eno; Pradnyani, Ni Luh Putu Sri Purnama; Suryantari, Eka Putri (Pertapsi-Indonesia collaborated with Petra Christian University, 2025)
Business sustainability is a business that continues to experience growth from time to time by utilizing business resources and competitive capabilities. This study aims to determine the effect of financial technology, financial literacy, and financial inclusion on the business sustainability of MSMEs. The research method used is quantitative research, with primary data obtained from questionnaire data measured on a Likert scale. The sampling technique used was snowball sampling. The population and sample in this study were active MSME players who used financial technology services in as many as 100 MSMEs in the Badung Regency. Data analysis using multiple linear regression with data presentation assisted by the SPSS 26 application. The results of this study indicate that financial technology has a positive and significant effect on business sustainability, financial literacy has a positive and significant impact on business sustainability, and financial inclusion has a positive and significant effect on the business sustainability of MSMEs in Badung Regency.